On the local boundedness of maximal H-monotone operators. (January 2017) - Balogh, Z.M.; Calogero, A.; Pini, R.
Abstract: In this paper we prove that maximal H-monotone operators T : H n ⇉ V 1 whose domain is all the Heisenberg group H n are locally bounded. This implies that they are upper semicontinuous. As a consequence, maximal H-monotonicity of an operator on H n can be characterized by a suitable version of Minty's type theorem.